EFEKTIVITAS TANAMAN BAMBU AIR (Equisetum hymale) TERHADAP LOGAM BERAT TIMBAL (Pb) PADA AIR LINDI (Leachate) - Manalu, Chindy Carolin; Aritonang, Christina; Sihotang, Frianty; Saragih, Jeremiah; Sari, Marlinda Nilan; Febriyossa, Adelia (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Leachate is water formed from piles of rubbish containing inorganic and organic compounds. One example of an organic compound that can cause environmental pollution is Pb (lead). Efforts to reduce levels of the heavy metal Pb are by carrying out phytoremediation using aquatic bamboo plants (Equisetum hymale). Methods: This research was conducted during September 2024 at the Green House, Medan State University, with leachate water samples taken from the Dendang Sea Final Waste Disposal Site (TPAS), Medan Tembung District, Deli Serdang Regency, North Sumatra Province. Methods used in the research This method uses descriptive or observational methods which are presented in the form of tables and graphs. Results: Research shows that water bamboo plants are able to absorb Pb levels in leachate water as seen from the parameters of changes in pH, temperature, color and physical condition of water bamboo plants. Conclusion: Water bamboo can be used as phytoremediation to reduce Pb levels in leachate waste.